Pendampingan Pembelajaran Al-Qur’an melalui Metode Tilawati dan Talaqqi di Rumah Qur'an Desa Tanah Merah, Kabupaten Tangerang: Assisted Qur’anic Learning through Tilawati and Talaqqi Methods at Rumah Qur’an, Tanah Merah Village, Tangerang Regency - Ansani Huannisa; Nadiyatul Lathifa; Zikron Fadhil Alhusaini; Ida Kurnia Shofa (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This community service activity was carried out at the Ummahat Class of Rumah Qur’an Tanah Merah as an effort to promote religious empowerment among housewives through assisted Qur’anic learning. The program was motivated by the limited Qur’an reading ability of adult learners, particularly in the articulation of Arabic letters, the application of tajwid rules, and low self-confidence when reciting the Qur’an in public. The aim of this community service was to improve participants’ Qur’anic reading quality while strengthening the role of Rumah Qur’an as a community-based center for religious development. A participatory approach was employed, consisting of preliminary observation, learning assistance, and reflective evaluation. The assistance integrated the Tilawati method for classical learning to enhance reading fluency and the Talaqqi method for individual guidance through direct correction. The results indicate a gradual improvement in participants’ Qur’anic reading accuracy, increased self-confidence, and the creation of a more supportive and sustainable learning environment. Overall, this community service demonstrates that appropriate and empathetic Qur’anic learning assistance can effectively enhance the religious quality of adult learners.